【答案】 证明: (1) 设 $C=0, D=-1, B=i$, $A=-1+i, \quad M=a i, \quad N=b(a, b \in R)$
A、M、N共线, 有 $\frac{A-M}{N-M} \in R$,

$\overrightarrow{D M}=1+a i, \overrightarrow{B N}=\frac{a}{1-a}-i$, 求得
$L$ $=$ $\frac{-a^2+a}{a^2-a+1}+\frac{a}{a^2-a+1} i=\frac{a}{a^2-a+1}(1-a+i)$
, $\overrightarrow{A N}=\frac{a}{1-a}+1-i=\frac{1}{1-a}-i$,
$\frac{\overrightarrow{A N}}{\overline{C L}}=\frac{\frac{1}{1-a}-i}{\frac{a}{a^2-a+1}(1-a+i)}=\frac{a^2-a+1}{a^2-a} i, \frac{a^2-a+1}{a^2-a} \in R\therefore C L \perp M N$
\begin{aligned} & \text { (2) } \overrightarrow{B N} \cdot i=1+\frac{a}{1-a} i, O=-\frac{1}{2}+\frac{1}{2} i, \overrightarrow{O N}=\frac{a}{1-a}+\frac{1}{2}-\frac{1}{2} i=\frac{1}{2}\left(\frac{1+a}{1-a}-i\right) \text {, } \\ & \overrightarrow{O M}=a i+\frac{1}{2}-\frac{1}{2} i=\frac{1}{2}+\left(a-\frac{1}{2}\right) i \\ & \overrightarrow{B N} \cdot i \cdot \overrightarrow{O N}=\left(1+\frac{a}{1-a} i\right) \frac{1}{2}\left(\frac{1+a}{1-a}-i\right)=\frac{1+a-2 a^2+(3 a-1) i}{2(1-a)^2} \\ & \overrightarrow{D M} \cdot \overrightarrow{O M}=(1+a i)\left[\frac{1}{2}+\left(a-\frac{1}{2}\right) i\right]=\frac{1+a-2 a^2+(3 a-1) i}{2} \\ & \therefore \frac{\overrightarrow{B N} \cdot i \cdot \overrightarrow{O N}}{\overrightarrow{D M} \cdot \overrightarrow{O M}}=\frac{1}{(1-a)^2}, \frac{\overrightarrow{B N} \cdot i}{\overrightarrow{D M}}=\frac{1}{(1-a)^2} \overrightarrow{\overrightarrow{O M}}, \overrightarrow{\overrightarrow{O N}}, \frac{1}{(1-a)^2} > 0 \\ & \text { 由 } B P \perp M N \text { 得 } \angle M O N=\arg \left(\frac{\overrightarrow{B N} \cdot i}{\overrightarrow{D M}}\right), \angle B P M=\arg \left(\frac{\overrightarrow{O M}}{\overrightarrow{O N}}\right) \\ & \therefore \angle M O N=\angle B P M 。 \end{aligned}